Cadmium and Phosphorous Fertilizers: The Issues and the Science - Roberts, Terry L. (Procedia engineering, 2014)
Non-nutritive metals, such as cadmium (Cd), occur naturally in all agricultural soils, in soil amendments (e.g. biosolids), and to varying degrees in phosphorous (P) fertilizers. Its persistence in the environment and its uptake and accumulation in the food chain make Cd a public health concern. The main effect of Cd on human health is kidney disease, and although other adverse effects have been reported (e.g. pulmonary, cardiovascular, and musculoskeletal systems), controversy exists regarding their effects. The only known case of Cd toxicity (i.e. itai-itai disease) occurred with subsistence farmers in Japan growing rice on soils contaminated with industrial wastes. Cadmium behaviour in soil and its accumulation by crops is complicated. Numerous factors (e.g. soil pH, organic matter content, salinity, macro and micronutrient fertilizers, crops species and cultivar, and tillage) influence the bioavailability and uptake of Cd by crops. Because fertilization increases the risk of Cd transfer to the food chain, some governments have imposed limits restricting the Cd content of P fertilizers. However, scientific risk assessments have shown that P fertilizer containing Cd is safe and does not pose risk to human health.